Study and Analysis of the Drying Kinetics of Jalapeño Pepper in a Convective Dryer - Jimenez, Santiago Linder Rubiños; Collana, Juan Taumaturgo Medina; Gamarra, Juan Herber Grados; Gonzales, Edwin Huarcaya; Gallegos, Eduardo Chavez; Fernandez, Victor Edgardo Rocha (International Journal of Membrane Science and Technology, 2023)
The high moisture content in jalapeno peppers (Capsicum annuum L.) can cause the growth and reproduction of microorganisms, making processing and long-term storage difficult. The objective of the research is to evaluate the kinetics of jalapeño pepper drying in a convective dryer. for this reason, the drying of the jalapeño pepper was carried out in a dryer with hot air at temperatures of 40, 50 and 70°C; obtaining the drying kinetic curves, the drying time that was 18, 31 and 41 respectively; the effective diffusivity was 2.924E-10m2.s-1 for the temperature of 40°C, 7.521 E-9 m2.s-1 for 50°C and 1.307 E-9 m2.s-1 for 70°C; the degree of correlation (R2) between the moisture content and the drying time was 0.994 at 70°C with a root mean square error (RMSE) of 0.0429, R2 of 0.990 at 50°C with a RMSE of 0.0216 and R2 of 0.993 at 40°C with an RMSE of 0.0162, so it is concluded that the criteria for a good adjustment of the drying model between the experimental temperature, as well as between the humidity rate and the drying time are met.